Efektifitas Video Edukasi Gizi Melalui Tiktok dan Instagram Terhadap Peningkatan Pengetahuan Anemia Pada Remaja Putri - Kariani, Ni Ketut; Ragil, Bimo; Masfufah, Masfufah (JUKEJ : Jurnal Kesehatan Jompa, 2025)
The lack of engaging nutrition education for adolescents oftenleads to poor food choices, contributing to a high incidence of anemia among adolescent girls. This study aims to determine the effectiveness of nutrition education videos delivered through tiktok and instagram in improving knowledge about anemia among female students at SMA 5 Palu. This study employed a pre-experimental design with a one-group pretest-posttest approach, involving 60 female students selected using the slovin formula from a population of 152 students. Data were collected using a knowledge questionnaire about anemia and analyzed using the paired T-Test.the results showed a significant improvement in knowledge scores after the intervention. In the TikTok group, the mean score increased from 29.7to 1.07 with a p-value of 0.000 ( p ≤ 0.05), while in the Instagram group, the mean score increased from 2.43 to 1.27 with a p-value of 0.004 ( p ≤ 0.05). The TikTok group demonstrated a greater improvement compared to the Instagram group. It can be concluded that nutrition education videos delivered through TikTok and Instagram effectively increase knowledge about anemia among adolescent girls, with TikTok showing higher effectiveness. The use of social media based nutrition education videos is recommended as innovative and youth-friendly strategy for health promotion.